Gender differences in time taken for peer review and publishing output in the physical sciences - Emma C. Leedham Elvidge (European Science Editing)
Background: Despite decades of work to improve gender equality in science (and other science, technology, engineering, and maths fields), gender bias still exists and has been shown to impact the retention of women in academic scientific careers. Publication of peer-reviewed articles remains a key criterion for career progression and a common marker of success in academia. Any barriers to publication faced by women may therefore impact their retention and career progression.Objectives: To investigate gender differences within one potential barrier to publication, namely the time taken in peer review, by investigating the question: ‘Is the peer review process longer for papers with (assumed) women as first authors than those with (assumed) male first authors?’Methods: Gender differences in peer review time were analysed for 1100 peer-reviewed papers published between 2006 and 2016 and selected from 5 journals covering a range of physical science disciplines and publication styles.Results: In the physical sciences, male first-authored papers outnumbered female first-authored papers 2:1. However, the analysis showed no statistical difference in the time taken for peer review between the two sets of papers.Conclusion: The time taken to peer review a paper is not linked to the gender of the paper’s first author. However, the large discrepancy in the number of papers with men as first authors compared to that with women as first authors could be a contributing factor to the attrition of women from the academic career ladder (the so-called ‘leaky pipeline’).